Cell lipid biology in infections: an overview - Prado, Luan Gavião; Camara, Niels Olsen Saraiva; Barbosa, Angela Silva (Frontiers in Cellular and Infection Microbiology, 2023)
Lipids are a big family of molecules with a vast number of functions in the cell membranes, within the cytoplasm, and extracellularly. Lipid droplets (LDs) are the most common storage organelles and are present in almost every tissue type in the body. They also have structural functions serving as building blocks of cellular membranes and may be precursors of other molecules such as hormones, and lipoproteins, and as messengers in signal transduction. Fatty acids (FAs), such as sterol esters and triacylglycerols, are stored in LDs and are used in β-oxidation as fuel for tricarboxylic acid cycle (TCA) and adenosine triphosphate (ATP) generation. FA uptake and entrance in the cytoplasm are mediated by membrane receptors. After a cytoplasmic round of α- and β-oxidation, FAs are guided into the mitochondrial matrix by the L-carnitine shuttle system, where they are fully metabolized, and enter the TCA cycle. Pathogen infections may lead to impaired lipid metabolism, usage of membrane phospholipids, and LD accumulation in the cytoplasm of infected cells. Otherwise, bacterial pathogens may use lipid metabolism as a carbon source, thus altering the reactions and leading to cellular and organelles malfunctioning. This review aims to describe cellular lipid metabolism and alterations that occur upon infections.